Strategi Literasi Digital Mendorong UMKM Elektronik Go Online - Yasmine Toshka Munawar Makyanie; Armanto Witjaksono (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to determine the effect of professionalism, experience, and level of education on the performance of young auditors in public accounting offices. The type of data used is primary data by distributing questionnaires to 74 respondents, all of them reside in Jakarta, Capital of Indonesia. Data were analyzed by multiple linear regression using SPSS version 19. The results of this study indicate that professionalism and experience have a significant effect on young auditor performance, while education level has no effect on young auditor performance. Thus, it can be concluded that the higher the professionalism and experience of an auditor, the better the performance, while the higher the level of education is not necessarily the better the performance. This research contribution is for young auditor professionalism and experience is more important than education level. For education institutions, this research suggests them to pay more attention upon soft skills (professionalism) beside technical skills. For employers this research insists during selection to emphasize on professionalism and experience of candidates rather than their educational background.